Potential of reused textile and cartridge-based filter for enhanced water filtration efficiency - Haiduchok, Oleksandr; Shestopalov, Oleksii; Kanunnikova, Nadiia; Tomashevskyi, Roman; Sakun, Antonina; Vorobiov, Bohdan; Kniazieva, Hanna; Kriuchkova, Valeriia; Kulinich, Sergii; Titov, Andrii (Polskie Towarzystwo Inżynierii Ekologicznej (PTIE), 2025)
This study examines the efficiency of combining reused textile materials (cotton, satin) with cartridge filters in mechanical water purification processes. Experiments were conducted on model suspensions with varying particle size distributions and concentrations. The findings demonstrate that an additional textile layer enhances fine-particle and adhesive contaminant retention, increasing overall filtration efficiency by 15–20% and preventing rapid pore clogging of the cartridge filter. It was shown that cotton and satin fabrics improve water quality and reduce operational and replacement costs for the primary filter element. Prospective research directions include developing standardized methods for fabric selection, evaluating textile filter durability under actual conditions, and improving end-of-life management strategies. Using reused textiles in water treatment systems proves to be both eco-friendly and cost-effective, especially in resource-constrained settings or emergencies.
Keywords: reused textile; cartridge filter; mechanical water purification; solid phase; fine particles; environmental safety